HOPE AGAINST DESPAIR: Reading Cronin in Times of Global Pandemic - Kusumalyam, Joseph Varghese (Journal of Dharma, 2020)
A. J. Cronin is a man who possessed a near-monastic silence in life and neither sought nor encouraged celebrity status. He embellishes the literary world with his creative genius and holds an important position among all modern English writers. Critics hail Cronin for his surer pen and more penetrating eye as his writing addresses many of the most distressing issues we face today. His books are celebrated for their honesty and realism. Cronin's experience as a doctor enabled him to bring out a literary treatment of an epidemic in 1941, six years before Albert Camus published The Plague. Caught in the sweeping tides of the Second World War, the world was swamped with hatred and meaninglessness, strangled by fear and crushed beneath the terror of the arms race. This was a time when people had lost faith in themselves, faith in everything, and nations of the world were fighting against each other. With the current situation of the world being not too dissimilar, Father Francis Chisholm’s story may give readers an answer to what the world can turn to for the survival during a pandemic. This paper focuses on analysing the human quest for meaning and happiness in absurdity, incredulity, uncertainty, and meaninglessness through a reading of A. J. Cronin’s 1941 novel, The Keys of the Kingdom. Same as COVID-19 works as an act and a process, Father Chisholm’s life too epitomises the process meaningfully.